The effect of the market on stock's spread: the case of the Athens Stock Exchange - Αγγελίδης, Τιμόθεος; Μπένος, Αλέξανδρος (SPOUDAI Journal of Economics and Business, 2005)
This paper presents a portfolio trading model which attempts to explain changes in market spread due to general market conditions. For 18 large and 13 medium capitalization stocks in the Athens Stock Exchange (ASE), we estimate the adverse selection and the order handling component of the bid-ask spread as well as the probability of a same side trade continuation based on a portfolio model of price formation which combines the work of Madhavan et al. (1997) and Huang and Stoll (1997). We find that, information coming out of the movements of the general ASE index does not affect significantly the low cap stocks, while there are indications this is not the case for high capitalization shares. JEL Classifications: D4, C1